Standard Quality Characteristics and Efficacy of a New Third-Generation Antivenom Developed in Colombia Covering Micrurus spp. Venoms (2024)
In Colombia, Micrurus snakebites are classified as severe according to the national clinical care guidelines and must be treated with specific antivenoms. Unfortunately, these types of antivenoms are scarce in certain areas of the country and are currently reported as an unavailable vital medicine. To address this issue, La Universidad de Antioquia, through its spin-off Tech Life Saving, is leading a project to develop third-generation polyvalent freeze-dried antivenom. The goal is to ensure access to this therapy, especially in rural and dispersed areas. This project aims to evaluate the physicochemical and preclinical parameters (standard quality characteristics) of a lab-scale anti-elapid antivenom batch. The antivenom is challenged against the venoms of several Micrurus species, including M. mipartitus, M. dumerilii, M. ancoralis, M. dissoleucus, M. lemniscatus, M. medemi, M. spixii, M. surinamensis, and M. isozonus, following the standard quality characteristics set by theWorld Health Organization (WHO). The antivenom demonstrates an appearance consistent with standards, 100% solubility within 4 min and 25 s, an extractable volume of 10.39 mL, a pH of 6.04, an albumin concentration of 0.377 mg/mL (equivalent to 1.22% of total protein), and a protein concentration of 30.97 mg/mL. Importantly, it maintains full integrity of its F(ab′)2 fragments and exhibits purity over 98.5%. Furthermore, in mice toxicity evaluations, doses up to 15 mg/mouse show no toxic effects. The antivenom also demonstrates a significant recognition pattern against Micrurus venoms rich in phospholipase A2 (PLA2) content, as observed in M. dumerilii, M. dissoleucus, and M. isozonus. The effective dose 50 (ED50) indicates that a single vial (10 mL) can neutralize 2.33 mg of M. mipartitus venom and 3.99 mg of M. dumerilii venom. This new anti-elapid third-generation polyvalent and freeze-dried antivenom meets the physicochemical parameters set by the WHO and the regulators in Colombia. It demonstrates significant efficacy in neutralizing the venom of the most epidemiologically important Micrurus species in Colombia. Additionally, it recognizes seven other species of Micrurus venom with a higher affinity for venoms exhibiting PLA2 toxins. Fulfilling these parameters represents the first step toward proposing a new pharmacological alternative for treating snakebites in Colombia, particularly in dispersed rural areas, given that this antivenom is formulated as a freeze-dried product.